2015
DOI: 10.1016/j.ijscr.2015.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Rectal metastasis from Breast cancer: A rare entity

Abstract: HighlightsIn patients with history of Invasive lobular cancer of breast with positive faecal occult blood with or without bowel symptoms should have high clinical suspicion of bowel metastasis.Breast cancer is the second most common cancer to metastasise to anywhere along the gastrointestinal tract from oropharynx to anus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Isolated metastases to the bowel wall are rare but have been reported secondary to a wide range of malignancies, including breast cancer [2][3][4][5][6][7][8][9][10][11][12]. In fact, after melanoma, breast cancer is the second most common metastasis to the GI tract [2]. Lobular carcinoma is the most likely to metastasize to the GI tract, despite representing only a minority of breast cancers [8].…”
Section: Discussionmentioning
confidence: 99%
“…Isolated metastases to the bowel wall are rare but have been reported secondary to a wide range of malignancies, including breast cancer [2][3][4][5][6][7][8][9][10][11][12]. In fact, after melanoma, breast cancer is the second most common metastasis to the GI tract [2]. Lobular carcinoma is the most likely to metastasize to the GI tract, despite representing only a minority of breast cancers [8].…”
Section: Discussionmentioning
confidence: 99%
“…The GI tract is a relatively uncommon site of metastasis for breast cancers, and accounts for less than 1% of all metastatic cases 4. Several papers have been published on gastric metastasis and their association with ILC of the breast 2 5.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies report spread to the rectum with only 14 cases found in a literature review in 2012 6. In many of these cases, including a further report in 2015,4 the lobular cell type has been implicated at histopathological diagnosis 3 8–12. Large bowel stenosis and stricture, as was evident on colonoscopy of our patient, has been described in several case reports and may be a reason for clinical presentation 4 6 11…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis to the gastrointestinal (GI) tract is uncommon, mainly if breast is the primary site; clinical manifestations are usually non-specific with symptoms related to local factors and extension of the bowel involvement. [1][2][3][4][5][6][7][8][9] Breast cancer affects lymph nodes, bones, lungs, liver, brain, and soft tissues, but rectal spread is very rare. [2][3][4][5][6][7][8][9] Lobular carcinoma is a major subtype in GI implants with up to 18% of incidence.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Breast cancer affects lymph nodes, bones, lungs, liver, brain, and soft tissues, but rectal spread is very rare. [2][3][4][5][6][7][8][9] Lobular carcinoma is a major subtype in GI implants with up to 18% of incidence. 1,2,[4][5][6][7][8][9] The period between the primary tumor diagnosis and evidence of implants is variable and reported to be up to 30 years.…”
Section: Introductionmentioning
confidence: 99%